1997
DOI: 10.1007/bf02867962
|View full text |Cite
|
Sign up to set email alerts
|

Lipid abnormalities in chronic renal failure

Abstract: :Lipid abnormalities remain to be a major cause of early mortality in patients with chronic renal failure (CRF). In present study, 114 (one hundred fourteen) CRF patients without any additional cause of dyslipidemia were divided into groups on the basis of etiologies of CRF. Blood samples from each group were analyzed for total cholesterol, triglyceride and HDL cholesterol along with blood urea nitrogen and serum creatinine. 25 healthy individuals without any obvious disease were taken as control. Patients fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…In the present study we find high levels of LDL cholesterol in group 1 and 2 which were not statistically significant when compared to controls. Similar results are forwarded by Bhagwat et al (10). However, levels were significantly low in goup 3 when compared to controls.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study we find high levels of LDL cholesterol in group 1 and 2 which were not statistically significant when compared to controls. Similar results are forwarded by Bhagwat et al (10). However, levels were significantly low in goup 3 when compared to controls.…”
Section: Discussionsupporting
confidence: 88%
“…There are western studies that showed hypercholesteremia (6) no hypercholesteremia (7) in CKD. However, there are only a few Indian studies (8,9,10) which have explored the atherogenic lipid profile at all the stages of CKD. The present study was undertaken to explore the altered lipid, lipoprotein and apoprotein abnormalities along with Lp(a) in CKD from stage I to stage V (ESRD) classified as per National Kidney Foundation Kidney Disease Outcomes Quality Initiative (NKFK/DOQI) guidelines (1) which plays a vital role in development of atherosclerotic cardiovascular disease.…”
Section: Introductionmentioning
confidence: 98%
“…A study by Bhagwat et al, 1997 observed dyslipidemia to be independent of serum creatinine levels [20]. Values of LDL-C showed decreasing trends in CKD stage 4 and 5 [22].…”
Section: Summarizing the Observations In Various Stages Of Ckdmentioning
confidence: 99%
“…23,24 To reduce cardiovascular mortality due to dyslipidemia in CKD patients, early management with statins has been recommended by several studies. [25][26][27] Rhee et al recommended to follow guidelines and risk assessment before start of treatment of dyslipidemia. 28 Several studies have observed significant dyslipidemias as a major risk factor for CVD in non-diabetic CKD patients on hemodialysis and on conservative therapy.…”
Section: Introductionmentioning
confidence: 99%